Managing the Congestion for Delivering and Receiving Truck Container at the Tanjung Priok Terminal by Analyzing the Congestion at Koja Container Terminal - Ayutia, Yolla; P Sirait, David; Salsabila Maligasach, Shiela; Ramadhani, Rafi; Hamdi, Ahmad; Krisnawati, Siti (KnE Social Sciences, 2023)
This study aimed to analyze the congestion that occurred around the Koja Container Terminal to develop strategies that will aid in managing the congestion presently occurring at the Tanjung Priok Container Terminal. Dwelling time, ship delay, gate server down, equipment damage, and lack of support for the truck arrival system were some causes of congestion in the Tanjung Priok area. There was an improvement in the truck arrival system (TAS) and Chassis Exchange Terminal (CET). Analyzing the inefficiency in managing the arrival of trucks for container pickup is the strategy needed for controlling congestion. This research was conducted by observing the field movements at the Koja Container Terminal and interviewing the people who experienced congestion in the terminal. This methodology was proposed to aid in efficiently operating the Tanjung Priok Port and alleviate truck congestion. Because it provides systematic, structured, and problem-solving benefits, this study is expected to be a source of consideration for stakeholders when making decisions. The result of this study will help improve the management of congestion at Terminal Koja. Keywords: Managing Congestion, Delivering and Receiving, Truck Container, Terminal Container, Port